Pirate latitudes : a novel - Crichton, Michael, 1942-2008. (New York : Harper, 2009)
The Caribbean, 1665. Pirate captain Charles Hunter, with backing from a powerful ally, assembles a crew of ruffians to take the Spanish galleon, "El Trinidad," guarded by the bloodthirsty Cazalla, a favorite commander of the Spanish king himself.
Map on lining papers.
Keywords: Pirates -- Fiction; Governors -- Fiction; Piracy -- Fiction; Hijacking of ships -- Fiction; Jamaica -- History -- 17th century -- Fiction; Adventure fiction; Historical fiction